The Municipal Liquidity Facility - Andrew Haughwout; Ben Hyman; Or Shachar (Federal Reserve Bank of New York, 2021)
At the onset of the COVID-19 pandemic, state and local governments were among the sectors expected to experience the most severe distress. The combination of a sharply deteriorating revenue picture, a pressing need for additional expenditures, delays in the receipt of substantial taxes owed, and an inability to access the financial markets raised serious concerns among many observers about the ability of state and local governments to meet their public service delivery responsibilities. In April 2020, the Federal Reserve announced the establishment of the Municipal Liquidity Facility (MLF) to help municipalities manage the cash flow challenges that the pandemic produced. The MLF ultimately offered three-year loans at penalty rates to a set of eligible municipal issuers that included states, large cities and counties, and a number of revenue bond issuers. Research suggests that the MLF, in spite of lending to only the State of Illinois and the Metropolitan Transportation Authority, contributed to a healing in the municipal securities market as a whole. Effects on real economic outcomes like employment in the sector are harder to attribute to facility.
Keywords: G14; G18; H74; 330; municipal debt; state and local governments; COVID-19; Federal Reserve lending facilities